Pakistan research repository: a showcase of theses and dissertations. Issue 4 (27th May 2014) - Ullah, Ahsan; Rafiq, Muhammad
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to describe the characteristics and purposes of Pakistan Research Repository (PRR). A quantitative analysis of this repository is carried out by analyzing the content of the repository. A critical analysis of the entire growth strategy, population and web interface is also included in this paper. This study also proposes certain measures to make it more effective and efficient for archiving the research output of a nation. The study was designed to investigate issues relating to PRR and outline steps to develop a strategy to overcome these challenges. Design/methodology/approach – This article focuses on quantitative aspects and critical analysis of PRR. A multi-tier research design was used to meet the objectives of the study. A web search was conducted, and information was drawn from documents available on the Web site of Higher Education Commission (HEC) of Pakistan, PRR and directories of open-access repositories; data were complemented by quantitative and critical analysis of the content of the repository. Information was also gathered by literature-based review of project documents which were created for the implementation of this project. Findings – The paper has highlighted how far this repository has succeeded in bringing the research output from universities across Pakistan to the researcher community by analyzing the available content by institution, type, subject and year. This study has provided a valuable insight about the current status of PRR by identifying gaps in the content of the repository. The quantitative analysis of the repository shows that the creation of this repository was a landmark achievement, as it provided the opportunity to researchers, faculty and students for preserving, disseminating and furthering their existing knowledge at a national-level platform. Research limitations/implications – This research article is a case study and focuses on PRR only. Therefore, researchers are encouraged to throw light on other repositories in Pakistan and sharing of resources among institutional repositories in Pakistan. Practical implications – This study will be helpful for the administrative authorities of HEC and university faculty to plan for effective collection of content from the institutions and digitization of this content. The paper includes implications for the development of repositories at an institutional level in Pakistan. Social implications – This paper will help in managing PRR, and it will ultimately lead to enhance and better manage research output in Pakistan. Originality/value – This paper has identified the characteristics and purposes for creating a research repository at the national level and provided a critical view of policies and statistical view of the content of the repository.